The geothermal potentials for electric development in Maluku Province - Vijaya Isnaniawardhani; Emi Sukiyah; Adjat Sudradjat; Martha Magdalena Nanlohy (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
The characteristic of small to medium size islands is the limited amount of natural resources for electric generation. Presently the needs of energy in Maluku Province are supplied by the diesel generation units. The electricity distributes through an isolated grid system of each island. There are 10 separate systems in Maluku Province, namely Ambon, Namlea, Tual, Saumlaki, Mako, Piru, Bula, Masohi, Dobo and Langgur. From the geothermal point of view, this condition is suitable because the nature of the generation is small to medium and the locations are dispersed. The geological condition of Maluku Province is conducive for the formation of geothermal resources. The advanced utilization of geothermal energy in Maluku Province is in Tulehu located about 8 kilometers NE of Ambon. It is expected that 60 MW electric will be produced at the first stage in 2019. A total of 100 MW resources were estimated. Other places of geothermal potentials are Lauke and Tawen both located in Ambon Island with the potentials of 25 MW respectively. In Oma Haruku, Saparua and Nusa Laut the geothermal potentials were estimated to be 25 MW each. The total amount of geothermal energy in Maluku Province is thus, 225 MW which will contribute significantly to the needs of projected 184 MW in the year 2025.